Kesejahteraan Masyarakat Transmigrasi di Kanagarian Penyubarangan - Elsa Meta Megawati; Azmi Fitrisia (Jurnal Kronologi, 2019)
This research is a socio-economic history study which aims to describe the process of the arrviral of transmigration communities in Kanagarian Panyubarangan (Trimulya) and describe the socio-economic development of transmigration communities in Kanagarian Panyubarangan (Trimulya) Dharmasraya Regency from 1983-2018. This research includes the research of history, and therefore this research follows the history of the method are: (1) heuristic are searching and collecting information from primary and secondary sources, (2) criticism of sources including internal and external criticism, that is whit a test of the authencity of the source or specified materials, (3) interpretasion which interprets activity data that has been collected and (4) historiography is stage presentation of research results in the form of scientific work. The results of this research revealed that the process of the arrival of transmigrants in Kanagarian Panyubarangan began in March 1983 in the form of general anad local transmigration, then followed in 1988 by independent self-directed transmigrants. The transmigration community at the beginning of the placement experienced many economic difficulties, access to education and transportation. To meet the need of he community, they must work as laborers and migrate to the other countries. The point of development of the transmigration community is seen from the increase in income. Supported by the results of oil palm plantations, the economic revival of the transmigration community can be seen from the place of residence, transportation facilities and education of their children.